La ronde des prisonniers - Santomauro, Sandra; Guerrero Gómez, Ana (Il sogno della farfalla, 2022)
A certain percentage of detainees in Italian prisons are people who, suffering from psychosis, have committed a crime. In their case, the task of the psychiatrist or psychologist becomes considerably more difficult. This occurs specifically when in addition to medical treatment and psychological support, their intent is to establish a psychotherapeutic relationship with the aim to cure. This article discusses some aspects of psychotherapy in prison including: the existence or absence of a genuine request for treatment; the risk of simulation with the aim to obtain secondary advantages; atypical settings; the limits of unconscious processing within a poor relational context; the discontinuity of therapy because of judicial reasons (prison transfer or end of sentence). A brief reference is devoted to the Covid-19 pandemic and the subsequent riots.